Finanzparlament - Alexander Dilger (Universität Münster, Institut für Organisationsökonomik, 2025)
Ein Finanzparlament oder vergleichbares Gremium anderen Namens würde finanzielle Entscheidungen treffen oder zumindest kontrollieren für seine jeweilige Organisation, sei diese ein Staat, eine internationale Vereinigung oder ein Verein. Stimmrechte für ein Finanzparlament würden nicht nach Köpfen vergeben, sondern nach den Zahlungen an die Organisation, z. B. Steuern, Beiträge oder Spenden. Dies würde die Geldgeber stärker einbinden, könnte die Einnahmen steigern und die finanziellen Entscheidungen verbessern. – – A financial parliament or a similar body by another name would make or at least supervise financial decisions for its respective organisation, be it a state, an international association or a club. Voting rights for a financial parliament would not be awarded per capita, but according to payments to the organisation, e.g. taxes, contributions or donations. This would involve payers more, could increase revenue and improve financial decisions.
Keywords: D71; D72; H20; H40; H60; H70; K16; L31; P16; 650; Demokratie; Fiskalpolitik; Liberalismus; Repräsentation; Stimmrechte